Three-year performance of inlay-retained or wing-retained zirconia resin-bonded fixed partial dentures: results from a randomized clinical pilot study - Bömicke, Wolfgang; Rathmann, Friederike; Rammelsberg, Peter; Zenthöfer, Andreas (Journal of dentistry, 2025)
Objective - The objective of this prospective clinical study was to compare the 3-year clinical outcome of 3-unit fixed-fixed zirconia resin-bonded fixed partial dentures (RBFPDs) with two different retainer designs placed in the posterior region. - Methods - Thirty patients with a single missing second premolar, first, or second molar were randomly assigned to receive either an inlay-retained (IR) (n = 15, mean age 56.4 years, 66.7% male) or a wing-retained (WR) RBFPD (n = 15, mean age 45.9 years, 46.7% male) made of monolithic zirconia (Cercon ht, DeguDent). The restorations primarily replaced first molars and were cemented using a self-etching resin cement (ED Primer + Panavia 21, Kuraray) after tribochemical silica coating (Rocatec, 3M ESPE) and silanization (Clearfil Ceramic Primer, Kuraray). Follow-ups were conducted at 1 week, 3 and 6 months, and 1, 2, and 3 years. Failure-free and intervention-free survival (success) probabilities were assessed using Kaplan-Meier statistics and log-rank tests; FDI criteria scores were compared using Fisher’s exact test (α = 0.05). - Results - Twenty-eight patients completed the 3-year follow-up. One patient with an intact IR RBFPD withdrew for health reasons, and 1 WR RBFPD failed due to unilateral debonding at 3 months. At 3 years, failure-free survival was 100% for IR and 93.3% for WR RBFPDs (P = 0.317). Success was 72.7% for IR and 86.7% for WR RBFPDs (P = 0.379), with no significant differences in FDI scores (P ≥ 0.098). - Conclusions - No short-term difference was found in the survival and success rates of monolithic zirconia RBFPDs for minimally invasive restoration of missing posterior teeth, whether retained by inlays or wings. (clinicaltrials.gov registration no.: NCT01997710) - Clinical significance - Monolithic zirconia RBFPDs retained by either inlays or wings appear to be a viable option for the esthetic and functional, albeit minimally invasive, restoration of missing posterior teeth in patients with abutment teeth are largely defect-free, with the wing retainer being preferred over the inlay retainer in intact teeth because it is less invasive.